Radio science techniques for deep space exploration - Asmar, Sami W. (Deep-space communications and navigation series., 2022)
"Radio signals are used to communicate information between robotic space missions throughout the solar system and stations on Earth. These signals are altered in their electromagnetic properties between transmission and reception due to propagation effects caused primarily by intervening media as well as forces acting on the spacecraft. When observed for their scientific potential, such alternations can provide very valuable information about the nature and environment of the planetary bodies or solar system targets under exploration. This also applies to signals transmitted from one spacecraft and received at another, in the case of multi-spacecraft missions. The media that the radio links propagate through include planetary atmospheres, ionospheres, rings, plasma tori, cometary material, or the solar corona. The Doppler shift to the frequency of the signals caused by the relative motion between the spacecraft and ground stations, or any transmitter-receiver combination, can contain scientific information about the gravitational forces acting on the spacecraft resulting from the bulk mass, density distribution, and global interior structure of the planets or moons, among other effects"--